Patients’ Experience of Anxiety and Pain during Retrobulbar Injections prior to Vitrectomy - Michael Mimouni; Hamza Abualhasan; Kamal Mtanes; Fares Mazzawi; Yoreh Barak (Journal of Ophthalmology)
Purpose. The purpose of this study was to evaluate the correlation between pain associated with retrobulbar block and anxiety levels before the injection. Methods. This prospective observational, noninterventional study included consecutive patients who received a retrobulbar block by a single surgeon prior to undergoing 25G PPV at the Department of Ophthalmology, Rambam Health Care Campus, between April 2016 and August 2017. Patients plotted their anxiety levels (scale 0–10) using the visual analogue scale for anxiety (VASA), and immediately after receiving the injection, they plotted their experienced level of pain (scale 0–10) using the visual analogue scale for pain (VAS), with scores ≥7 defined as severe. Results. Overall, 48 eyes of 48 patients aged 68.4 ± 10.3 years were included, of which 62.5% were of male gender. Severe anxiety and pain were experienced by 10.4% and 12.5%, respectively. There was a significant correlation between VASA and VAS scores (r = 0.43, p=0.002) with no other preprocedural parameters demonstrating a significant association with the VAS score. In multivariate analysis, the VASA score was the only factor that was significant (p=0.01), and a patient with a severe VASA score was 20 times more likely of experiencing severe pain (p=0.006). The ROC curve analysis revealed an area under the curve of 0.89 (p<0.001), and a VASA score >4 demonstrated a sensitivity of 83.3% and a specificity of 73.8% in predicting severe pain. Conclusions. Approximately 10% of patients experience severe anxiety and pain during retrobulbar blocks. Considering the importance of compliance, reducing anxiety and premedication may be considered, particularly in high-risk patients (VASA score > 4).